Improved Prodigiosin Production by Relieving CpxR Temperature-Sensitive Inhibition - Sun, Yang; Wang, Lijun; Pan, Xuewei; Osire, Tolbert; Fang, Haitian; Zhang, Huiling; Yang, Shang-Tian; Yang, Taowei; Rao, Zhiming (Frontiers in Bioengineering and Biotechnology, 2020)
Prodigiosin (PG) is a typical secondary metabolite mainly produced by Serratia marcescens. CpxR protein is an OmpR family transcriptional regulator in Gram-negative bacteria. Firstly, it was found that insertion mutation of cpxR in S. marcescens JNB 5-1 by a transposon Tn5G increased the production of PG. Results from the electrophoretic mobility shift assay (EMSA) indicated that CpxR could bind to the promoter of the pig gene cluster and repress the transcription levels of genes involved in PG biosynthesis in S. marcescens JNB 5-1. In the ΔcpxR mutant strain, the transcription levels of the pig gene cluster and the genes involved in the pathways of PG precursors, such as proline, pyruvate, serine, methionine, and S-adenosyl methionine, were significantly increased, hence promoting the production of PG. Subsequently, a fusion segment composed of the genes proC, serC, and metH, responsible for proline, serine, and methionine, was inserted into the cpxR gene in S. marcescens JNB 5-1. On fermentation by the resultant engineered S. marcescens, the highest PG titer reached 5.83 g/L and increased by 41.9%, relative to the parental strain. In this study, we revealed the role of CpxR in PG biosynthesis and provided an alternative strategy for the engineering of S. marcescens to enhance PG production.